Pengaruh Komposisi Media Tanam Dan Konsentrasi Pupuk Organik Cair Pada Pertumbuhan Bibit Tanaman Bitti: The Effect of Planting Media Composition and Liquid Organic Fertilizer Concentration on the Growth of Bitti Plant Seedlings - Musyawal, Afdhal (Jurnal Kehutanan dan Lingkungan, 2025)
AFDHAL MUSYAWAL 24011014015. The Effect of Planting Media Composition and Liquid Organic Fertilizer Concentration on the Growth of Bitti Plant Seedlings. Supervised by: Andi Abdul Rahman Syafar and Fikram Fahrumansyah. This study aims to analyze and examine the effect of planting medium composition and liquid organic fertilizer concentration on the growth of bitti plant seedlings. This study was conducted in the form of a two-factor factorial experiment based on a randomized block design. The first factor was the composition of the planting medium, which consisted of three levels: topsoil + charcoal husks + manure (2:1:1), topsoil + charcoal husks + manure (1:1:1), and topsoil + charcoal husks + manure (1:1:2). The second factor was the concentration of liquid organic fertilizer, which consisted of three levels: 5% concentration (50 ml POC + 950 ml water), 10% concentration (100 ml POC + 900 ml water), and no liquid organic fertilizer. The results showed that the planting medium consisting of topsoil + charcoal husks + manure in a ratio of 2:1:1 (M1) had a better effect on the height increase of bitti 2 MST seedlings (1.44 cm) and bitti 4 MST seedlings (2.21 cm). Meanwhile, a 10% concentration of liquid organic fertilizer (POC) (100 ml POC + 950 ml water) had a better effect on the height increase of bitti seedlings at 2 MST (1.43 cm), while no POC treatment had a better effect on stem diameter at 8 MST (2.99 mm), stem diameter at 10 MST (3.35 mm), stem diameter at 12 MST (3.77 mm), and root volume (3.33 cubic cm). There was no interaction between the growing medium and the concentration of liquid organic fertilizer POC on the growth of bitti seedling